Doxorubicin hydrochloride and L-arginine co-loaded nanovesicle for drug resistance reversal stimulated by near-infrared light - Linping Jiang; Kesi Wang; Liyan Qiu (Elsevier, 2022)
Drug resistance is accountable for the inadequate outcome of chemotherapy in clinics. The newly emerging role of nitric oxide (NO) to conquer drug resistance has been recognized as a potential strategy. However, it remains a great challenge to realize targeted delivery as well as accurate release of NO at desired sites. Herein, we developed a PEGylated indocyanine green (mPEG-ICG) integrated nanovesicle system (PIDA) to simultaneously load doxorubicin hydrochloride (DOX⋅HCl) and the NO donor L-arginine (L-Arg), which can produce NO triggered by NIR light irradiation and exert multimodal therapy to sensitize drug-resistant cancers. Upon 808 nm irradiation, the NO released from PIDA led to a decrease in mitochondrial membrane potential, an increase in ROS and significant ATP depletion in K562/ADR cells, thus inhibiting cell growth and resolving the problem of drug resistance. Consequently, the in vivo experiment on K562/ADR-bearing nude mice indicated that PIDA nanovesicles achieved significant anticancer efficacy with a tumor inhibition rate of 80.8%. Above all, PIDA nanovesicles offer guidance for designing nanoplatforms for drug-resistant cancer treatment.